Students' Perceptions about Learning Difficulties on Fungi Materials - Nina Lutfia; Rani Suryani; Lesy Luzyawati; Suparto Suparto (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2022)
This study aimed to determine students' perceptions of learning difficulties in fungi material. This research method is qualitative, the population of this research is all students, totaling 199 people. The subjects of this study were students of class X MA Negeri 1 Indramayu for the academic year 2021/2022, totaling 67 people. The instruments used were questionnaires, field notes, and interviews. The sampling technique used is random. Data analysis used the Likert scale and percentage technique (%). The results showed that the average learning difficulties of class X students at MA Negeri 1 Indramayu were generally in the very high category with a percentage of 28.5% and 71.5% with low learning difficulties. The biggest factor causing learning difficulties comes from internal factors, namely interest and motivation indicators 70.83% (low), readiness and attention 72.08% (low). Followed by external factors, namely the school environment 73.75% (low).